The Circulation of Ionized Gas in the Milky Way Galaxy - Eagon, Andrew (Proceedings of the Wisconsin Space Conference, 2016)
We use the Wisconsin H-alpha Mapper (WHAM) all sky survey to observe kinematic properties of ionized interstellar gas in the Galaxy. WHAM’s survey is a velocity resolved map of the H-alpha emission from the Milky Way with a one-degree spatial resolution and 12.8 km s-1 velocity resolution. Using this data the first and second moments are calculated and mapped to provide insight on the kinematic properties of the Galaxy. This research was funded by the Wisconsin Space Grant Consortium and supported by the NSF REU site grant to the University of Wisconsin-Madison.